Dimensional Transformations of Guided-Mode Resonant Photonic Lattices - Akari Watanabe; Junichi Inoue; Kenji Kintaka; Shanwen Zhang; Shogo Ura; Robert Magnusson (IEEE Photonics Journal, 2020)
Reflection spectra based on guided-mode resonance (GMR) are simulated and discussed with transformation between one-dimensional (1-D) and two-dimensional (2-D) photonic lattices by introducing intermediate structures consisting of vertically-stacked 1-D and 2-D gratings. Dependences of reflection spectra on a 2-D fractional ratio are investigated for two examples of narrowband and broadband resonance elements. Observed complicated spectrum transformations for the narrowband example are successfully explained by combining simple models with guided-mode indices and multilayer reflection. The understanding of the fundamental transformation dynamics will aid in the reflection band engineering for development of new optical components.